F.11 Predictors of length of stay following lumbar fusion. (17th June 2016) - Lang, ST; Yavin, D; Dhaliwal, P; Steve, C; DuPlessis, S
Abstract : Background: Accurate prediction of length of stay (LOS) following elective lumbar fusion may help optimize the utilization of resources and may assist with physician and patient expectations. Methods: Outcomes were collected prospectively among patients undergoing elective lumbar fusion. Prolonged LOS was defined as ≥5 days. The influence of baseline and peri-operative characteristics on the odds of prolonged LOS was assessed by a multivariate logistic regression model. Results: 150 patients underwent elective lumbar fusion surgery. Patient characteristics were as follows: average age was 61.9, average pre-operative back pain measured by the visual analogue scale was 54.3, and 36.5% of patients were identified as having severe disability, defined by an Oswestry disability index over 40. The average LOS was 4.9 days, with 28% having a prolonged LOS. Majority of patients had one level fused (69.7%). The odds of prolonged LOS were increased by severe disability (odds ratio [OR] 3.58, p<0.005), levels fused (OR 2.52, p<0.005), greater than 70 years of age (OR 3.81, p<0.005), and any treatment related adverse event (OR 4.32, p <0.02). There was no significant influence of prolonged surgery (p=0.3) or pre-operative back pain (p=0.23) on LOS. Conclusions: Prolonged length of stay was significantly influenced by severe disability, levels fused, age > 70, and any adverse events.